Effects of drilling parameters on TI-6Al-4V alloy using different coolants - P.Srinivasa Rao; K.Siva Prasad; Roopsandeep Bammidi (Journal of Engineering & Processing Management, 2020)
The formulation or application of coolants plays a critical role in machining to bring out the best finished products. In this scientific article, the study focused on the effects of coolants and machining parameters of Ti-6Al-4V are investigated with consideration of their performances by using drilling operation. The design of ex- periments (DOE) was considered and the performance of machining was measured with respect to cutting temperatures and surface responses. The final results put forward that the excellent surface finish and minimal cutting temperatures are ob- tained by application of power metcut s plus when compared with pure water. The factors that impact the surface roughness of Ti-6Al-4V are coolant and feed rate. The coolant also helps in the machining process by reducing temperature at the cutting zone.
Keywords: Ti-6Al-4V; drilling; power metcut s plus; surface roughness; temperature